2007
DOI: 10.1523/jneurosci.4549-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Using Imagination to Understand the Neural Basis of Episodic Memory

Abstract: Functional MRI (fMRI) studies investigating the neural basis of episodic memory recall, and the related task of thinking about plausible personal future events, have revealed a consistent network of associated brain regions. Surprisingly little, however, is understood about the contributions individual brain areas make to the overall recollective experience. To examine this, we used a novel fMRI paradigm in which subjects had to imagine fictitious experiences. In contrast to future thinking, this results in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
588
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 651 publications
(668 citation statements)
references
References 43 publications
(133 reference statements)
54
588
3
6
Order By: Relevance
“…Sugiura et al 2005; figure 5). Moreover, there was no overlap between this simple object network (Sugiura et al 2005) and that of complex scene construction (Hassabis et al 2007a), suggesting that they represent dissociable cognitive processes with distinct neural bases. Nevertheless, complex scenes and experiences are clearly constructed out of simpler elements.…”
Section: The Construction Systemmentioning
confidence: 98%
See 4 more Smart Citations
“…Sugiura et al 2005; figure 5). Moreover, there was no overlap between this simple object network (Sugiura et al 2005) and that of complex scene construction (Hassabis et al 2007a), suggesting that they represent dissociable cognitive processes with distinct neural bases. Nevertheless, complex scenes and experiences are clearly constructed out of simpler elements.…”
Section: The Construction Systemmentioning
confidence: 98%
“…We have demonstrated that scene construction is a dissociable set of processes supporting the episodic memory system (Hassabis et al 2007a), both past and future, but what are some of the other processes that together with the construction system underpin the special properties of episodic memory? We addressed this question using our fMRI imagination paradigm by contrasting the recall of real memories to the recall of previously created imaginary memories matched for difficulty, age, detail and vividness, thus partialling out the effects of the common construction network (Hassabis et al 2007a).…”
Section: Add-ons To the Construction Systemmentioning
confidence: 98%
See 3 more Smart Citations